Establishment of a Real-Time Quantitative PCR Assay for Porcine Circovirus-Like Virus and the First Evidence of Its Spread to Hainan and Jiangxi Provinces of China - Zhang, Leyi; Zhang, Xinming; Xu, Ge; Wang, Lin; Liu, Xianhui; Zhang, Pengfei; Wang, Shuangyun; Liang, Tairun; Wang, Zhipeng; Liu, Yanling; Xu, Zheng; Li, Zan; et al. (Frontiers in Veterinary Science, 2022)
Porcine Circovirus-like (PCL) virus, a new emerging virus, has been widely detected in Guangdong, Guangxi and Anhui provinces in China, which may be a novel agent causing severe diarrhea in newborn piglets and tending to spread widely. Evidence suggests that the virus is related to hemorrhagic enteritis and diarrhea and many newborn piglets were emaciated to death after infection. Therefore, a sensitive, quick, and accurate detection system for virus detection and epidemiological investigation is necessary. In this study, we developed a real-time quantitative PCR assay based on SYBR green for the detection of PCL virus. The Cap conserved region of PCL virus was found by the alignment of the uploaded genome sequences to design specific primers, and the primers were tested and showed good specificity, sensitivity and reproducibility. 138 fecal samples were obtained from diarrheal pigs in South China from June to December 2021. 22.46% (31/138) of the samples and 40% (8/20) of the pig farms were positive for PCL virus respectively by using this method. Moreover, it is worth noting that the virus was first detected in Hainan and Jiangxi Provinces of China, which means that the virus may spread widely in China. Through evolutionary tree analysis and partial sequence comparison, there are some differences of virus genes in each province, suggesting that there is a risk of variation, and the four PCL virus strains showed a sequence similarity of 86.7%-87.8% for the rep gene and 92.2%-92.9% for the Rep protein respectively with Bo-Circo-like virus that is detected in bovine, which further demonstrates a close relationship between the two viruses that originated from different animals. In conclusion, our study provides a useful diagnostic approach for PCL virus detection and epidemiological inquiry. Meanwhile, the epidemic data using this real-time qPCR assay provides evidence for the widespread variations and epidemic of the virus in South China, and warns the appropriate measures for prevention and control of PCLV infection should be under consideration in pig production.